Livestock Handling and Transport 3rd Edition - Grandin, T (CABI, 2014)
The purpose of this book is to serve as a source of the latest scientific research information and as an archive of practical information. In this third edition, the goal is to bring together in one book the latest research data and practical information on animal handling, the design of facilities and transport. Some of the most valuable contributions to the knowledge of animal handling and transport are often located in producer publications that are difficult to obtain. The extensive reference lists in each chapter will help preserve important knowledge that may not be available on the Internet. At the end of the book there is an index of useful web pages on handling, behaviour and transport. The first edition was published in 1993 and this third edition was published 14 years later. It is fully updated with the latest research. An extensively revised introductory chapter covers the increasing awareness of animal welfare around the world and outlines the effective auditing programmes of large, corporate meat buyers. Three new authors have chapters on sheep transport, biosecurity and low-stress methods for sorting cattle and weaning calves. To provide an additional perspective on livestock management in South America, Asia, India and other regions, two new co-authors have been added to the chapters on cattle transport and the handling of cattle raised in close association with people. The best of the older material – including all the popular handling system layouts and behaviour diagrams – has been kept. Many readers reported that they found these diagrams useful.